100 Ways To Be Thankful - Gerry, Lisa (Wahington, DC : National Geographic Kids, 2019)
"Discover 100 creative ways to express gratitude for all that's good in your life with this powerful little book, packed with positive thoughts, practical ideas, and take-action prompts. Rejoice in snow days! Make time for belly laughs! Pause to marvel at the wonders of nature! In today's hectic, fast-paced, overscheduled world, so many of us -- including kids! -- try to do it all. This book offers up unique ways to slow down, be mindful, and appreciate life's little gifts. The pages are filled with inspiration and motivation on how to be appreciative and pass along kindness. Interviews with National Geographic explorers offer examples of ways to give back. Uplifting quotes and ideas are sure to motivate readers to do more and be more mindful every day, so we all come away with a renewed sense that life is pretty great!"--
OSLIS\Gale Nat Geo eBooks(2/2/23).
Includes index.
Age: 8-12.
Grade 4 to 6.
Description based on print version record.
Keywords: Gratitude -- Juvenile literature; Gratitude; JUVENILE NONFICTION -- Social Issues -- Values & Virtues; JUVENILE NONFICTION -- Social Issues -- Manners & Etiquette; JUVENILE NONFICTION -- Body, Mind & Spirit; Mindfulness (Psychology); Gratitude; Electronic books- OSLIS; Instructional and educational works; Juvenile works; Instructional and educational works; 2